Comparison of anesthetic efficacy of 4% articaine and 2% mepivacaine during maxillary molar extraction at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara - Ahyar Riza; Imtinan Ghina (Journal of Dentomaxillofacial Science, 2021)
Objective: To compare the efficacy of 4% articaine and 2% mepivacaine for local infiltration during maxillary molar extraction at Oral and Maxillofacial Surgery Department, Faculty of Dentistry, Universitas Sumatera Utara. Material and Methods: This was an experimental study with two group post-test only control group design. Sample were divided into 2 groups and each group consisted of 15 patients received 4% articaine and 2% mepivacaine. The time of onset of action were recorded using dental probe at intervals 15s and intra-operative pain were assesed using visual analog scale during the procedure. Results: The results were statistically analyzed using independent T-test. The comparison between 4% articaine and 2% mepivacaine showed significant difference in the mean of onset time (p = 0,00 < 0,05) and no significant differences in the intraoperative pain between 4% articaine and 2% mepivacaine for local infiltration during maxillary molar extraction (p = 0,78). Conclusion: Articaine 4% has clinically achieved faster onset, comparable to mepivacaine in infiltrative techniques for maxillary teeth extraction. However, there were no significant differences between them in relation to the intensity of intra-operative pain.